2022
DOI: 10.4103/jfmpc.jfmpc_288_21
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of CoVID-19 among health care professionals (HCPs) of tertiary care hospital of northern state of India

Abstract: Introduction: Current study was carried out as per the government of India and Himachal Pradesh guidelines to carry out a serosurvey to assess the extent of COVID-19 infection among health care professionals (HCPs) after 6 months of managing COVID-19 cases. Methods: A hospital-based survey was carried out among 1279 conveniently selected HCPs from September 2020 to January 2021. Results: The participants had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…7 similarly during SARS epidemic in 2004 HCWs comprised 20-40% of cases. 8 The data on nation by nation number of HCW infected with SARS Cov-2 and associated mortality is not clear as most countries do not make the data publicly available. A study was performed among members of the Infectious Diseases International Research Initiative found that although there were differences among the 37 countries that joined the survey; the median of the HCW deaths in 100,000 per population of the country was 0.05.…”
Section: Introductionmentioning
confidence: 99%
“…7 similarly during SARS epidemic in 2004 HCWs comprised 20-40% of cases. 8 The data on nation by nation number of HCW infected with SARS Cov-2 and associated mortality is not clear as most countries do not make the data publicly available. A study was performed among members of the Infectious Diseases International Research Initiative found that although there were differences among the 37 countries that joined the survey; the median of the HCW deaths in 100,000 per population of the country was 0.05.…”
Section: Introductionmentioning
confidence: 99%